Two new species of Tricorythodes Ulmer, 1920 (Insecta, Ephemeroptera) from Southeastern Brazil - Gonçalves, Inês C.; Da-Silva, Elidiomar R.; Nessimian, Jorge L. (Zootaxa, 2010)
Two news species of Tricorythodes are described from both, nymph and male imago: Tricorythodes chalaza sp. nov. and Tricorythodes diasae sp. nov. Imagoes of T. diasae sp. nov. can be characterized as follows: vein CuP of wings absent or incomplete; distal 3/4 of hind legs black; inner margins of styliger plate projected; penes rectangular with lateral margins sclerotized, forming two distal lobes inserted apico-dorsally with rounded margins whereas imagoes of T. chalaza sp. nov. present: vein CuP incomplete or absent; inner margins of styliger plate projected; basal swelling on segment II of forceps shaded with black; penes pyramidal with lateral margins sclerotized, divided apically.